IRRADIATION OF THE ADULTS AND PUPAE OF CALLOSOBRUCHUS MACULATUS (F.) FOR THE PRODUCTION OF STERILE MALES AND FEMALES - PAJNI, H.R.; CHEEMA, GURBIR (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1997)
Fresh adults and pupae of different ages were exposed to different doses of Gamma radiations for induction of sterility. Fresh and one-day to three-day old adults and two-day to four-day old pupae treated with 2000 and 2500 rads produced cent per cent sterile males and females, respectively. The exposure of freshly formed adults to a dose of 5000 rads produced 100% sterile females but maximum of 96.9% senile males were produced with a dose of 6000 rads,